Challenges of nurses in front of man´s health in basic care (Research, Society and Development, 2021)
It is known that there is a reduced frequency of male users in the Primary Care services, there are many assumptions for this to happen. Objective: this research aimed to describe the challenges faced by nurses working in primary care in relation to men's health. Method: It was a qualitative study, carried out with four nurses working in the Family Health Strategies, to whom a semi-structured interview script was applied, in June 2019. For data analysis, we opted for the use of the analysis of content of the narrative theme. Results: it was evidenced that social, cultural and institutional factors, and the non-implementation of the policy are among the reasons that contribute for men not to seek assistance in primary care services. Conclusion: Thus, it is concluded that it is necessary to promote men's health care in this context and that professional nurses working in primary care consider their uniqueness, in order to understand the policy and adopt strategies aimed at its effective implementation.